2021
DOI: 10.2807/1560-7917.es.2021.26.6.2000023
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus in young children: community cohort study integrating serological surveys, questionnaire and electronic health records, Born in Bradford cohort, England, 2008 to 2013

Abstract: Background Bronchiolitis caused by respiratory syncytial virus (RSV) is a major cause of mortality and morbidity in infants. Aim To describe RSV epidemiology in children in the community in a high-income setting. Methods We used stored blood samples from the United Kingdom Born in Bradford cohort study that had been collected at birth, age 1 and 2 years old, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(27 reference statements)
3
10
0
1
Order By: Relevance
“…In contrast, studies focusing on children with an infant RSV LRTI compare this group to those without an infant RSV LRTI, although the latter is a heterogenous group that includes children not infected with RSV in infancy and those who had milder RSV infections in the first year of life. In our study, using molecular and serologic testing to establish RSV infection or no infection during infancy, we found that ∼54% of children are infected with RSV in infancy, which is consistent with other studies 15,16 . Importantly, children without an infant RSV infection had a ∼26% lower risk of childhood asthma than those with an infant RSV infection.…”
Section: Does Infant Rsv Infection Cause Childhood Asthma?supporting
confidence: 90%
“…In contrast, studies focusing on children with an infant RSV LRTI compare this group to those without an infant RSV LRTI, although the latter is a heterogenous group that includes children not infected with RSV in infancy and those who had milder RSV infections in the first year of life. In our study, using molecular and serologic testing to establish RSV infection or no infection during infancy, we found that ∼54% of children are infected with RSV in infancy, which is consistent with other studies 15,16 . Importantly, children without an infant RSV infection had a ∼26% lower risk of childhood asthma than those with an infant RSV infection.…”
Section: Does Infant Rsv Infection Cause Childhood Asthma?supporting
confidence: 90%
“…Regarding the number of siblings in a family, some recent studies have suggested that this may represent a risk factor because of a small-scale crowding effect [15] , due to the exchange of pathogens. However, it is reasonable to presume a loss of significance of this risk factor during the lockdown period, since every member of the family experienced less social interaction, thus decreasing the potential contact with pathogens [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the features that contribute to RSV replication, fitness, and transmissibility is important for understanding the outcomes of infection and disease intervention approaches. RSV infects young children, with many experiencing more than one infection by 2 years of age [1,2]. Globally, RSV causes acute respiratory infection in infants and young children, leading to >60,000 in-hospital deaths and >3 million hospital admissions per year in children <5 years old [3].…”
Section: Overview Of Rsvmentioning
confidence: 99%